Association of racism experience with gun purchase during COVID-19: Evidence from a national survey in the United States - Dejun Su; Khalid Alshehri; Brooke Lawson (Preventive Medicine Reports)
Objective: Concurrent with a substantial surge in gun purchases among Americans during COVID-19, there was an escalation of racism and hate crimes in the United States. Despite this disturbing trend, little is known about whether and the extent to which racism experience is linked to gun purchase during the pandemic. This study aims to examine the association between experience of racial discrimination and gun purchase among Americans during COVID-19. Methods: Based on data from the Health, Ethnicity, and Pandemic Survey (n = 2,584), a national survey conducted in the U.S. in October 2020, chi-square tests and logistic regressions were estimated to examine the association between racism experience and gun purchase during COVID-19 with and without controlling for selected covariates. Results: About 6.9 % of the sample reported gun purchases during COVID-19. Among respondents who reported experience of racism, 18.3 % purchased a gun as compared to 5.8 % among those who did not report experience of racism. Relative to respondents with no experience of racism, the odds of gun purchase for those who reported racism experience became 257 % as much (AOR = 2.57, 95 % CI: 1.63, 4.04) after controlling for other covariates in the analysis. Non-Hispanic Blacks were more likely to report gun purchases than non-Hispanic Whites (AOR = 1.80, 95 % CI: 1.04, 3.10). Conclusions: Americans who reported experience of racism during COVID-19 were far more likely to purchase a gun than those otherwise. These findings elevate the need for addressing racism as an important risk factor of firearm violence.